Managing Supply Chain Flexibility using an integrated approach of classifying, structuring and impact assessment. (10th December 2010) - More, Dileep; Subash Babu, A.
Flexibility in the Supply Chain (SC) has emerged as a new strategic tool to enhance business excellence. The exploitation of flexibility is vital in designing, planning and controlling SC system to improve an organisation's ability to recover from disruptions. There are various types of SCF, each type comes in various forms and each of which can be implemented in different ways and with different costs. The topic of Supply Chain Flexibility (SCF) has drawn the attention of the researchers and practitioners over a decade. However, in literature, there is no evidence of any study focused on interdependency among various types of SCF types. An attempt has therefore been made to identify and analyse relationships among the SCF types, to establish contextual relationships among them to identify the factors that are relevant to various SCF types and to evaluate the dynamics among them. The details of the study are reported in this paper.